Mapa Del Perú - A. Raimondi (My University, 1988)
Map of the Department of Loreto and its border with the Brazilian border country.

Mapa del Departamento de Loreto y su límite con el país fronterizo con Brazil
Map of Peru
Keywords: Límite Del Perú; Límite De Loreto; División de Departamento; Provincia; Brazil; Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps